THE USES OF DIFFERENTIAL COSTS. - Sanders, T. H. (The Accounting Review, 1929)
The attention of economists, accountant and business men has of late been directed more and more to the behavior of overhead costs, and in particular to those consequences which result from the fixed character of a large part of them. Everyone is familiar with the fact that an increased volume of output results in a decreased unit cost, as far as overhead is concerned. But another economists used the term differential costs to indicate those specific increments of expense which will accompany any specific increment in the output. Before analyzing this theory, or presenting any practical applications of it, the relation of differential costs to other economic concepts ought to be considered. Another economic concept which is related to differential costs, though inversely so, is the idea of quasi-rent. This term is employed to include all those extra earnings derived from the possession of rare natural abilities on the part of a business man. It follows that producers will be earning high quasirents when their production costs are low and low quasi-rents when their production costs are high, thus making an inverse ratio between quasi-rent and costs.